Pemberian Diversi dalam Proses Penyidikan Tindak Pidana terhadap Anak Berkebutuhan Khusus - Adi Sylvia Intan Pramesti Eas; Noenik Soekorini; Sri Astutik; Vieta Imelda Cornelis (SENTRI: Jurnal Riset Ilmiah, 2026)
Diversion for children with disabilities needs to be properly understood, considering that the implementation of diversion requires the perpetrator to meet and consult with the victim. Communication is key to successful diversion. Furthermore, understanding the perpetrator, namely the child with a disability, cannot be ignored. Investigations of crimes committed by children with special needs continue to refer to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and other relevant laws and regulations. However, adjustments and special attention to the conditions of children with special needs during the investigation process are necessary to ensure the fulfillment of their rights and the best interests of the child. While the principle of legal certainty remains the foundation, investigations of children with special needs who commit crimes must be conducted with attention to the child's special needs. Diversion is based on the principle of restorative justice, which emphasizes restoring relationships between the perpetrator, victim, and community. Implementation of Diversion for Children with Special Needs: Identifying Special Needs: It is important to identify the child's special needs, such as intellectual disabilities, physical disabilities, or other developmental disorders.